On the Merits of Targeted and Individualized Physical Exercise in Persons with Diabetic Foot Disease—From Controversies to Consensus - Edyta Sutkowska; Anna Korzon-Burakowska; Karolina Biernat (Biomedicines)
Exercise is a cornerstone of diabetes management, but the onset of diabetic foot disease (DFD) can significantly limit its implementation. Meanwhile, physical activity (PA) has been shown to reduce the risk of developing DFD through various mechanisms, and emerging evidence also supports the role of exercise in managing the active phase of the condition. Appropriately tailored PA offers both local and systemic benefits—even in clinical contexts where foot offloading is recommended. The research indicates that selected exercises can be safely incorporated into care plans, providing therapeutic effects without compromising wound healing. Drawing from current knowledge based on basic science, clinical research, and relatively general recommendations, this article summarizes the local and systemic effects of properly selected exercises in patients with DFD. It explains the underlying mechanisms and briefly discusses practical examples, integrating the most recently published findings.